Refractory Duodenal Ulcer in a Patient With Median Arcuate Ligament Compression - Bronze, Sérgio Manuel Tubal (2024)
© 2024 The Author(s). Published by Wolters Kluwer Health, Inc. on behalf of The American College of Gastroenterology.